DNA damage response and apoptosis induced by hyperthermia in human umbilical cord blood lymphocytes. (June 2021) - Zastko, Lucián; Petrovičová, Petra; Račková, Anna; Jakl, Lukáš; Jakušová, Viera; Marková, Eva; Belyaev, Igor
Abstract: While hyperthermia (HT) is a promising modality for cancer treatment, the knowledge on mechanisms of its effect on cells is still limited. We have investigated DNA double-strand break (DSB) and apoptosis induced by HT. Umbilical cord blood lymphocytes (UCBL) were subjected to HT at 43 °C. We have treated cells for 1 h ( 1 h HT ), 2 h ( 2 h HT ) and by combined HT and ice treatment (both lasting 1 h). Enumeration of DSB by 53BP1/γH2AX DNA repair focus formation and early apoptosis by γH2AX pan-staining was conducted by automated fluorescent microscopy. Apoptotic stages and viability were assessed by the annexin/propidium iodide (PI) assay using flow cytometry 0, 18, and 42 h post-treatment. HT induced either immediate ( 2 h HT ) or postponed ( 1 h HT ) DNA damage. The levels of 53BP1 and γH2AX foci differed under the same treatment conditions, suggesting that the ratio of co-localized γH2AX/53BP1 foci to all γH2AX and also to all 53BP1 foci could be a valuable marker. The ratio of co-localized foci increased immediately after 2 h HT regardless the way of assessment. For the first time we show, by both annexin/PI and γH2AX pan-staining assay that apoptosis can be induced during or immediately after the 2 h HT treatment. Our results suggest that HT may induce DSB in dependence on treatment duration and post-treatment time due to inhibition of DNA repair pathways and that HT-induced apoptosis might be dependent or associated with DSB formation in human lymphocytes. Assessment of γH2AX pan-staining in lymphocytes affected by HT may represent a valuable marker of HT treatment side effects. Highlights: Mild hyperthermia induces DNA damage and apoptosis in dependence on its duration. Foci co-localization ratio assessment – additional tool for DNA damage specification γH2AX pan-staining indicates hyperthermia-induced apoptosis in human lymphocytes.